Sexy ang mommy ko My mommy is sexy - Matias, Segundo D.; Doctolero, Beth Parrocha; Bravo, Becky; Garcia, Edith (Maynila Lampara Publishing House, Inc., 2010)
"Find out in this story how Nicole's mommy becomes sexy in her own eyesat the best medicine is for children's ailments, and who alone in the world can provide it."
"Stories with moral values."
Text in English and Filipino.
Keywords: Children's stories, Philippine (English)